2022
DOI: 10.3390/antiox11071265
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Quercetin and Its Methylated Derivatives 3-o-Methylquercetin and Rhamnazin in Lipopolysaccharide-Induced Inflammation in Porcine Intestinal Cells

Abstract: Oxidative stress in the small intestine can lead to inflammation and barrier malfunction. The present study describes the effect of quercetin (Q), 3-o-methylquercetin (QM), and rhamnazin (R) on cell viability, paracellular permeability, production of intracellular reactive oxygen species (ROS), extracellular hydrogen peroxide (H2O2), and interleukin-6 (IL-6) after challenging jejunal cells (IPEC-J2) with different types (Salmonella enterica ser. Typhimurium, Escherichia coli O111:B4, and E. coli O127:B8) of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
(77 reference statements)
1
3
1
Order By: Relevance
“…The Amplex red method, in contrast to DCF, is only suitable for the detection of H 2 O 2 , whereas the latter is a non-selective ROS detecting method. In IPEC-J2 cells, LPS of various origins could not increase H 2 O 2 levels [ 38 ] using Amplex red method which is in good agreement with our present findings. Other mycotoxins such as DON and T2 toxin and their combination could increase EC H 2 O 2 in IPEC-J2 cells, which returned to control levels in the presence of rosmarinic acid [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…The Amplex red method, in contrast to DCF, is only suitable for the detection of H 2 O 2 , whereas the latter is a non-selective ROS detecting method. In IPEC-J2 cells, LPS of various origins could not increase H 2 O 2 levels [ 38 ] using Amplex red method which is in good agreement with our present findings. Other mycotoxins such as DON and T2 toxin and their combination could increase EC H 2 O 2 in IPEC-J2 cells, which returned to control levels in the presence of rosmarinic acid [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in a combined incubation of quercetin and TNFα, quercetin was able to mitigate the barrierweakening effect of TNFα. Also, in IPEC J2 cells, different incubation challenges were performed and showed a barrier-protective effect of quercetin against barrier perturbation by, e.g., lipopolysaccharide (LPS) [59] or deoxynivalenol (DON) [60,61]. In contrast to our IPEC J2 results, Pomothy [60] and Li et al [61] observed an increased TEER due to quercetin incubation without any challenge.…”
Section: Discussioncontrasting
confidence: 79%
“…Quercetin (C 15 H 10 O 7 ), a flavonoid, is abundantly present in vegetables and fruits as a secondary antioxidant metabolite [ 38 ]. Quercetin has a strong antioxidant capacity, which gives it a perfect preventive and therapeutic effect on diseases caused by oxidative stress [ 55 ]. The antioxidant property of quercetin was previously proven in the porcine intestine in vitro and in vivo experiments.…”
Section: Plant-derived Polyphenol Application To Counteract Oxidative...mentioning
confidence: 99%
“…Using a specific inhibitor of Nrf2 (all-trans-retinoic acid), the authors further demonstrated that the protective effect of quercetin on enterocytes was mediated via activating the Nrf2 signaling pathway and redox homeostasis [ 60 ]. Karancsi et al (2022) reported the protective impact of quercetin and its methylated derivatives on inflammation in IPEC-J2 cells, acting against the lipopolysaccharide challenge [ 55 ]. A dosage of 50 μM quercetin or its methylated derivatives all decreased intracellular ROS levels, extracellular H 2 O 2 levels, and IL-6 levels of IPEC-J2 cells challenged with lipopolysaccharide [ 55 ].…”
Section: Plant-derived Polyphenol Application To Counteract Oxidative...mentioning
confidence: 99%
See 1 more Smart Citation